2007
DOI: 10.1515/epoly.2007.7.1.1536
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Dynamic Mechanical Properties of Hydrogenated Nitrile Butadiene Rubber and the Effect of Peroxide Cross-linkers

Abstract: Abstract:The viscoelastic behavior of hydrogenated nitrile butadiene rubber (HNBR) was studied over a range of temperatures and shear frequencies. Dynamic mechanical properties were studied and modelled using the generalized Maxwell model and the Williams-Landel-Ferry equation. A fitting algorithm was developed to provide the best agreement between the experimental data and the model results. In addition to dynamic mechanical analysis (DMA), differential scanning calorimetry (DSC) was applied. The HNBR structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The free-volume parameters K 1,HPAB /γ HPAB and K 2,HPAB − T g,HPAB may be calculated using the following expressions: K 2 , HPAB false( normalν false) T g , HPAB false( normalν false) = C 2 , HPAB false( normalν false) T g , HPAB false( normalν false) K 1 , HPAB false( normalν false) / γ HPAB false( normalν false) = HPAB * false( normalν false) / false( ln false( 10 false) C 1 , HPAB false( normalν false) C 2 , HPAB false( normalν false) false) where C 1,HPAB and C 2,HPAB represent the degree of cure-dependent Williams−Landel−Ferry (WLF) parameters, while T g,HPAB was taken as the reference temperature. C 1,HPAB and C 2,HPAB were for differently cross-linked HPAB calculated according to the procedure presented in our previous work, where the glass transition temperatures presented in Figure were applied as the reference temperatures for differently cross-linked HPAB. K 1,HPAB /γ HPAB and K ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free-volume parameters K 1,HPAB /γ HPAB and K 2,HPAB − T g,HPAB may be calculated using the following expressions: K 2 , HPAB false( normalν false) T g , HPAB false( normalν false) = C 2 , HPAB false( normalν false) T g , HPAB false( normalν false) K 1 , HPAB false( normalν false) / γ HPAB false( normalν false) = HPAB * false( normalν false) / false( ln false( 10 false) C 1 , HPAB false( normalν false) C 2 , HPAB false( normalν false) false) where C 1,HPAB and C 2,HPAB represent the degree of cure-dependent Williams−Landel−Ferry (WLF) parameters, while T g,HPAB was taken as the reference temperature. C 1,HPAB and C 2,HPAB were for differently cross-linked HPAB calculated according to the procedure presented in our previous work, where the glass transition temperatures presented in Figure were applied as the reference temperatures for differently cross-linked HPAB. K 1,HPAB /γ HPAB and K ...…”
Section: Resultsmentioning
confidence: 99%
“…The pycnometer liquid was chosen on the basis of its properties, predominantly polarity, so that it simultaneously granted relatively good wetting of a compound and prevented too intensive swelling of the latter. Compound density was calculated from reference liquid density and the weight of a compound, pycnometer, pycnometer/reference liquid, and pycnometer/reference liquid/compound …”
Section: Methodsmentioning
confidence: 99%
“…Using these considerations, a total of six rate constants for all potential substituents had to be determined, that is k iha,i,j,k,l,m,n , k iar,i,j,k,l,m,n,o , k ha,i,j,k,l,m,n , k p,i,j,k,l,m,n,o , k t,i,j,k,l,m,n, and k b,i,j,k . The rate constants and the associated activation energies and preexponential factors were determined utilizing molecular modeling [52,53]. This was achieved by the semiempirical Parameterized Model number 3 (PM3) method calculations, using unrestricted Hartree-Fock (UHF) spin pairing and self-consistent field controls of 0.001 convergence limit and 1000 iterations limit.…”
Section: Resultsmentioning
confidence: 99%
“…Specimens were prepared by stamping them prior to any exposure from a sheet material to a geometry of approximately 2 mm  2 mm  50 mm, although the test gauge length for DMA was 45 mm. The specimens were cyclically loaded in torsion at a strain amplitude of 0.1% and a frequency of 1 Hz during a constant temperature ramp of 0.64 K min À1 from À60 C to 180 C. This temperature ramp yielded a data collection interval of approximately 2 K. It has been reported that HNBRs are highly sensitive to strain rate and heating rate [24]; in this work, the heating rate was constant and the results presented here are for a single strain rate. Preliminary tests (not presented here) included testing of specimens at various strain ranges and revealed that a strain amplitude of 0.1% was a suitable strain range to test these specimens, and showed that the stress vs. strain response was linear in this region, and no variation of shear modulus resulting from the Payne Effect [20] was detectable.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 99%